Syphilis - a disease that still occurs - Ben Rhaiem, Rami; Kępka, Przemysław; Kuziemkowska, Daria; Kuźma, Jan; Łącka-Majcher, Anna; Łokczewska-Bojar, Aleksandra; Tarsa, Grzegorz; Skotalczyk, Magdalena; Sawińska, Zuzanna; Sudelska, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction: Syphilis is a systemic disease caused by Treponema pallidum. Humans are the only hosts, and the incubation period lasts from 9-90 days. Currently it can be divided into congenital or acquired. This division is due to the moment in which the infection occurred. Congenital Syphilis- when the infection happens during the prenatal period, whereas acquired, when the infection took place in the period after birth. In early acquired syphilis the I and II stages can be distinguished as well as early latent syphilis. As defined, early latent syphilis includes an acquired infection up to 1 or 2 years back, depending on the guidelines. Late syphilis however includes: late latent syphilis, tertiary syphilis, late cardiovascular syphilis, late neurosyphilis. Congenital syphilis has also been divided into early (which includes the first 2 years) as well as late, which is characterised by signs of congenital syphilis, the so-called stigmata of congenital syphilis constituting the untreated infection during the fetal stage or the infancy stage. Aim of the Study: The aim of our study is to divert the attention to one of the sexually transmitted diseases, which despite the downward trend at the end of the 20th century, rebounded at the beginning of the 21st century, especially among men who have sexual contact with other men. We paid attention to the symptoms accompanying this disease, also in the context of congenital syphilis, as well as the different methods of pharmacological treatment according to European guidelines. Materials and methods: Reviewed literature available at scientific articles , Google Scholar using keywords: “syphilis – epidemiology”, “syphilis treatment”, “symptoms of syphilis”, as well as European guidelines regarding the treatment of syphilis.